Mononuclear transition metal complexes with sterically hindered carboxylate ligands: Synthesis, structural and spectral properties - Kannan, Sethuraman; Venkatachalam, Galmari; Lee, Ha-Jin; Min, Byoung Koun; Kim, Woong; Koo, Eunhae; Do, Young Rag; Yoon, Sungho (PERGAMON-ELSEVIER SCIENCE LTD, 2011)
The metal coordination geometry in the active site of metalloproteins are very different from the one of small inorganic complexes, due to the inflexibility of the ligand set from amino acid side chains different from freely moving ligand set in synthesis. Using the sterically hindered 2,6-di-(p-fluorophenyl)benzoate(L) ligand, a series of mononuclear Co(II), Ni(II) and Cu(II) complexes of general formula [M(L)(2)(Hdmpz)(2)] (where, Hdmpz = 3,5-dimethyl pyrazole) have been synthesized and characterized by the variety of spectroscopic methods. A distorted octahedral geometry in case of nickel, tetrahedral geometry for cobalt and square pyramidal in copper was observed in the X-ray studies, which also revealed that the uncoordinated oxygen atom of the carboxylate group forms intramolecular hydrogen bonding with the N-H group of the coordinated 3,5-dimethylpyrazole in case of cobalt and copper. Crown Copyright (C) 2010 Published by Elsevier Ltd. All rights reserved.
Keywords: BIOLOGICALLY IMPORTANT PEPTIDES; MOLECULAR-STRUCTURE; CRYSTAL-STRUCTURE; DIIRON ENZYMES; ACTIVE-SITES; M-TERPHENYLS; NICKEL(II); CHEMISTRY; CENTERS; BINUCLEAR